2005
DOI: 10.1152/jn.00724.2005
|View full text |Cite
|
Sign up to set email alerts
|

Photic-Induced Sensitization: Acquisition of an Augmenting Spike-Wave Response in the Adult Rat Through Repeated Strobe Exposure

Abstract: J Neurophysiol 94: 3925-3937, 2005; doi:10.1152/jn.00724.2005. It is well established that patterns of sensory input can affect neuroplastic changes during early development. The scope and consequences of experience-dependent plasticity in the adult are less well understood. We studied the possibility that repeated exposure to trains of stroboscopic stimuli could induce a sensitized and potentially aberrant response in ordinary individuals. Chronic electrocorticographic recording electrodes enabled measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Epileptic seizure in photosensitive epilepsy patients is most frequently induced by 15 Hz flicker stimulus when the eyes are open 80 and 10 Hz stimulus when the eyes are closed 81 , which can confirm the resonance nature of epileptic seizures. Based on this hypothesis, one can also expect to induce seizure in animal models more effectively by choosing the stimulation frequency close to the resonance frequency of their brains 82 , 83 . In addition, factors and conditions that change the brain state to a relatively lower frequency and higher amplitude oscillations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Epileptic seizure in photosensitive epilepsy patients is most frequently induced by 15 Hz flicker stimulus when the eyes are open 80 and 10 Hz stimulus when the eyes are closed 81 , which can confirm the resonance nature of epileptic seizures. Based on this hypothesis, one can also expect to induce seizure in animal models more effectively by choosing the stimulation frequency close to the resonance frequency of their brains 82 , 83 . In addition, factors and conditions that change the brain state to a relatively lower frequency and higher amplitude oscillations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results here demonstrate that dLGN TBS-induced LTP can dramatically enhance both visual acuity and contrast sensitivity, at least at the level of the VEP, across a wide range of stimulus orientations. Recent work has suggested that it is possible to non-invasively induce LTP in primary sensory cortices of rats (Manning et al, 2007; Uhlrich et al, 2005) and humans (Clapp et al, 2005a; Clapp et al, 2005b) using photic or auditory tetani. Another alternative may be the use of transcranial magnetic stimulation (TMS), either on its own or in conjunction with visual stimulation, to non-invasively deliver a potentiating tetanus (see (Cooke and Bliss, 2006) for review).…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the gradual reduction in information flow-through with increased internal weight strength will be asymptotic: at the most extreme, the highly interconnected network will be epileptic and any input will ignite a seizure that is unrelated to the input (Uhlrich et al 2005). At a lower level of dynamic pathology, abnormalities in power and coordination in gamma bands might be seen, as has been noted in schizophrenia (Uhlhaas et al 2006; Spencer et al 2004, 2003; Uhlhaas and Singer 2006).…”
Section: Discussionmentioning
confidence: 99%